{![\frac{5}{2x-3y}+\frac{10}{3x-2y}=3 \frac{5}{2x-3y}+\frac{10}{3x-2y}=3](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2x-3y%7D%2B%5Cfrac%7B10%7D%7B3x-2y%7D%3D3)
{![\frac{20}{3x-2y}-\frac{15}{2x-3y}=1 \frac{20}{3x-2y}-\frac{15}{2x-3y}=1](https://tex.z-dn.net/?f=%5Cfrac%7B20%7D%7B3x-2y%7D-%5Cfrac%7B15%7D%7B2x-3y%7D%3D1)
Замена:
![2x-3y=a;3x-2y=b 2x-3y=a;3x-2y=b](https://tex.z-dn.net/?f=2x-3y%3Da%3B3x-2y%3Db)
Получаем систему:
{![\frac{5}{a}+\frac{10}{b}=3 \frac{5}{a}+\frac{10}{b}=3](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7Ba%7D%2B%5Cfrac%7B10%7D%7Bb%7D%3D3)
{![\frac{20}{b}-\frac{15}{a}=1 \frac{20}{b}-\frac{15}{a}=1](https://tex.z-dn.net/?f=%5Cfrac%7B20%7D%7Bb%7D-%5Cfrac%7B15%7D%7Ba%7D%3D1)
ОДЗ: a≠0; b≠0
{
\frac{10a+5b-3ab}{ab}=0" alt="\frac{5}{a}+\frac{10}{b}=3=>\frac{10a+5b-3ab}{ab}=0" align="absmiddle" class="latex-formula">
{
\frac{20a-15b-ab}{ab}=0" alt="\frac{20}{b}-\frac{15}{a}=1=>\frac{20a-15b-ab}{ab}=0" align="absmiddle" class="latex-formula">
a≠0; b≠0 =>
{![10a+5b-3ab=0 10a+5b-3ab=0](https://tex.z-dn.net/?f=10a%2B5b-3ab%3D0)
{![{20a-15b-ab=0 {20a-15b-ab=0](https://tex.z-dn.net/?f=%7B20a-15b-ab%3D0)
Второе уравнение умножим на (-3)
{![10a+5b-3ab=0 10a+5b-3ab=0](https://tex.z-dn.net/?f=10a%2B5b-3ab%3D0)
{![{-60a+45b+3ab=0 {-60a+45b+3ab=0](https://tex.z-dn.net/?f=%7B-60a%2B45b%2B3ab%3D0)
Сложим:
![10a+5b-3ab-60a+45b+3ab=0 10a+5b-3ab-60a+45b+3ab=0](https://tex.z-dn.net/?f=10a%2B5b-3ab-60a%2B45b%2B3ab%3D0)
![-50a+50b=0 -50a+50b=0](https://tex.z-dn.net/?f=-50a%2B50b%3D0)
![-50a=-50b -50a=-50b](https://tex.z-dn.net/?f=-50a%3D-50b)
![a=b a=b](https://tex.z-dn.net/?f=a%3Db)
Подставим в первое уравнение a=b и получим:
10a+5a-3a^2=0" alt="10a+5b-3ab=0=>10a+5a-3a^2=0" align="absmiddle" class="latex-formula">
-3a(a-5)=0" alt="-3a^2+15a=0=>-3a(a-5)=0" align="absmiddle" class="latex-formula">
не удовлетворяет ОДЗ
a_2=5;" alt="a-5=0=>a_2=5;" align="absmiddle" class="latex-formula">
Получаем:
a=b=5
Обратная замена:
![2x-3y=5;3x-2y=5 2x-3y=5;3x-2y=5](https://tex.z-dn.net/?f=2x-3y%3D5%3B3x-2y%3D5)
Решаем систему:
![\left\{{{2x-3y=5}\atop{3x-2y=5}}\right. \left\{{{2x-3y=5}\atop{3x-2y=5}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B2x-3y%3D5%7D%5Catop%7B3x-2y%3D5%7D%7D%5Cright.)
![\left\{{{2x-3y=5}|*(-3)\atop{3x-2y=5}|*2}\right. \left\{{{2x-3y=5}|*(-3)\atop{3x-2y=5}|*2}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B2x-3y%3D5%7D%7C%2A%28-3%29%5Catop%7B3x-2y%3D5%7D%7C%2A2%7D%5Cright.)
![\left\{{{-6x+9y=-15}\atop{6x-4y=10}}\right. \left\{{{-6x+9y=-15}\atop{6x-4y=10}}\right.](https://tex.z-dn.net/?f=%5Cleft%5C%7B%7B%7B-6x%2B9y%3D-15%7D%5Catop%7B6x-4y%3D10%7D%7D%5Cright.)
Сложим:
![-6x+9y+6x-4y=-15+10 -6x+9y+6x-4y=-15+10](https://tex.z-dn.net/?f=-6x%2B9y%2B6x-4y%3D-15%2B10)
![5y=-5 5y=-5](https://tex.z-dn.net/?f=5y%3D-5)
![y=-5:5 y=-5:5](https://tex.z-dn.net/?f=y%3D-5%3A5)
![y=-1 y=-1](https://tex.z-dn.net/?f=y%3D-1)
Подставим в первое:
2x-3*(-1)=5" alt="2x-3y=5=>2x-3*(-1)=5" align="absmiddle" class="latex-formula">
![2x=5-3 2x=5-3](https://tex.z-dn.net/?f=2x%3D5-3)
![2x=2 2x=2](https://tex.z-dn.net/?f=2x%3D2)
![x=1 x=1](https://tex.z-dn.net/?f=x%3D1)
![x=1;y=-1 x=1;y=-1](https://tex.z-dn.net/?f=x%3D1%3By%3D-1)
Ответ: {1; -1}